Protected homes, according to the HoNOS scale, in patients with psychiatric disorders,2022 - Lira Camargo, Washington Melvin; Lozano Zanelly, Glenn Alberto; Hurtado Concha, Aristides; Rivera Gonzales, Maria Marleny; Zamalloa Torres , Ana Maria; Lira Camargo, Zoila Rosa (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The objective of this research work was to determine the effectiveness of sheltered homes in global functioning according to the HoNOS scale. Methodology, is of a quantitative, quasi-experimental type of research.The research discusses with Herrera et al (2018), finding improvement in functionality in the patients of the Protected Homes. Conclusion, global functioning of the residents improved from 15 points on average in the pre-test of the patients to 5 in the post-test, evidencing an improvement in global functioning.